Perbandingan Efisiensi Panci Bahan Aluminium dan Besi untuk Memanaskan Air - Ni Nyoman Juniantari Mediasih Landuh; Gusti Ayu Gita Sarawati; Ni Made Lidya Suari; Amelia Sihombing; Eirenne Pridari Sinsya Dewi (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
This study aims to compare the thermal efficiency of two aluminum and iron-based pans in the water heating process. This research method uses a mixed approach that includes direct observation (qualitative) and quantitative analysis based on changes in water temperature after heating at two volume variations, namely 0.25 L and 0.5 L. Heating was carried out with two time differences, the total of each experiment was four experiments, with two experiments for five minutes and also two experiments for ten minutes. The results showed that iron pans produced heat of 66,150 J at a volume of 0.25 L and 151,200 J at a volume of 0.5 L. Meanwhile, an aluminum pan could produce heat of 53,550 J at a volume of 0.25 L and 67,200 J at a volume of 0.5 L. The difference in heat value was influenced by the thermal conductivity and physical characteristics of each material. This study provides an understanding of the thermal performance of both pot materials and can be considered in the selection of efficient cooking utensils in the household environment.